PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMPENSASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT TANTRI DELTA UTAMA - Ni Luh Sri Kasih; Gwah Pandita Agung (ARTHA SATYA DHARMA, 2023)
The phenomenon that occurs is based on observations from researchers at PT Tantri Delta Utama Singaraja, every employee is required to be able to carry out their duties quickly and precisely in achieving targets. This study aims to determine the effect of transformational leadership style, compensation, and work discipline on employee performance at PT Tantri Delta Utama Singaraja. This study used a questionnaire statistik collection technique (questionnaire). The population in this study were 44 employees of PT Tantri Delta Utama Singaraja and the head of the depot, the samples taken from this population were 43 employees. Respondents were dominated by men and adults aged 21 to 30 years. From the results of the study, it was found that (1) There is an influence of Transformational Leadership on employee performance. The transformational leadership style can motivate employees to achieve higher performance. (2) There is an effect of compensation on employee performance. Fair and competitive compensation can be a motivating factor for employees to improve employee performance. (3) There is an influence of work discipline on employee performance. Work discipline can increase the efficiency and effectiveness of employees in achieving the desired results.